2001
DOI: 10.1046/j.1445-5994.2001.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival on long‐term oxygen therapy in chronic airflow limitation: from evidence to outcomes in the routine clinical setting

Abstract: In routine practice, survival of unselected CAL patients with multiple comorbidities is less than that reported in the original RCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
47
5
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 13 publications
13
47
5
1
Order By: Relevance
“…MIYAMOTO et al [16] studied 9,759 patients with COPD, tuberculosis sequelae or chronic interstitial pneumonia receiving long-term oxygen therapy (LTOT) and reported a better survival for females than males. CROCKETT et al [17] studied a population of 505 COPD patients (256 females) also receiving LTOT and confirmed the previous findings. CROCKETT et al [17] also reported that the prognostic factors for females (age, FEV1, BMI and comorbidities) were different from those of males (only BMI).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…MIYAMOTO et al [16] studied 9,759 patients with COPD, tuberculosis sequelae or chronic interstitial pneumonia receiving long-term oxygen therapy (LTOT) and reported a better survival for females than males. CROCKETT et al [17] studied a population of 505 COPD patients (256 females) also receiving LTOT and confirmed the previous findings. CROCKETT et al [17] also reported that the prognostic factors for females (age, FEV1, BMI and comorbidities) were different from those of males (only BMI).…”
Section: Discussionsupporting
confidence: 73%
“…Four previous studies on highly selected patients with chronic respiratory failure and hypoxaemia have specifically addressed mortality differences between males and females. Three studies [16][17][18] indicated that females with COPD have a better prognosis than males, whereas one concluded the opposite [19]. MIYAMOTO et al [16] studied 9,759 patients with COPD, tuberculosis sequelae or chronic interstitial pneumonia receiving long-term oxygen therapy (LTOT) and reported a better survival for females than males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Japanese study of patients treated with LTOT for COPD, tuberculosis sequelae, or interstitial pneumonia showed significantly better survival in women, despite a higher average baseline Pa CO 2 (see Figure E1) (52). This finding was confirmed in a meta-analysis of LTOT in which a survival advantage also existed for women (53). However, Machado and coworkers reported in patients with COPD receiving LTOT that survival was significantly worse in females, those with lower body mass index, and lower Pa O 2 (54).…”
Section: Therapeutic Implicationssupporting
confidence: 69%
“…However, the difference in mortality between females and males persisted across disease severity. Conversely, we do agree with his comments regarding the more severe patients, especially those with hypoxaemia, as was previously shown by the works of the MIYAMOTO et al [2], CROCKETT et al [3] and FRANKLIN et al [4].…”
Section: From the Authorscontrasting
confidence: 42%